DIFFERENCES IN IFN-GAMMA AND SARS-COV-2 SPECIFIC IgG LEVEL IN mRNA BNT162B2 (PFIZER-BIONTECH) VACCINATED NAIVE AND COVID-19 RECOVERED INDIVIDUALS FROM ZAKHO DISTRICT, DUHOK, IRAQ - MOHAMMED, DILMAN IMAD; SULAIMAN, AZAD AHMED (Journal of Duhok University, 2023)
COVID-19 has caused massive public health threats worldwide, leading to the development of effective vaccines to control the epidemic. Real-world evidence confirms the efficacy of vaccinations against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This study aimed to evaluate and compare the titer of anti-SARS-CoV-2 IgG antibodies against the S1 subunit of the virus’s spike protein as a marker of the humoral response and the concentration of interferon-gamma as an indicator of cellular response in naive and recovered individuals. The study included 176 individuals, 88 (50%) were naïve, and 88 (50%) had a previous history of exposure to SARS-CoV-2 with or without symptoms. The serum concentration of IgG and IFN-γ were measured two weeks after the second dose of the BNT162B2 mRNA vaccine in naive and recovered individuals using enzyme-linked immunosorbent assays. The concentration of anti-SARS-CoV-IgG and IFN-γ was significantly higher in recovered participants compared to naive. Moreover, the concentration of anti-SARS-CoV-IgG and IFN-γ was significantly associated with severe cases. Our results suggested that the second dose of the BNT162b2 mRNA vaccine provides a protective humoral and cellular immune response to almost all individuals. While inducing a more robust immune response in recovered individuals, indicates that a single dose of the vaccine may be sufficient for symptomatic recovered individuals